Scouting Education as A Strategy to Strengthen Nationalist Values in Indonesian High School Student - Jamaludin Malik; Nasiwan Nasiwan (Journal of Mathematics Instruction, Social Research and Opinion)
This study explores how scouting education strategically strengthens nationalist values among Indonesian high school students. Employing a qualitative research design, the study was conducted at SMAN 1 Subang, Kuningan Regency, involving data collection through interviews, observations, documentation, and literature studies. The results indicate that scouting education programs at SMAN 1, Subang, are well integrated with the 2013 Curriculum, particularly in reinforcing spiritual attitudes, social attitudes, and practical skills aligned with Pancasila values. These programs are adaptively designed to respond to the dynamic needs of society, encouraging students to develop respect for religious diversity, teamwork, discipline, and social responsibility. Moreover, scouting activities such as national flag ceremonies, singing patriotic songs, and community service effectively cultivate students’ sense of nationalism. The study also highlights the role of civic education as a complementary reinforcement in building nationalist character through classroom instruction and extracurricular practices. Integrating civic values in scouting education provides a comprehensive foundation for fostering civic intelligence, participation, and responsibility. Therefore, scouting education is an extracurricular requirement and vital for character-building and nurturing future citizens committed to national unity and cultural diversity. Schools are encouraged to optimize and promote scouting education as a transformative platform for strengthening national identity among students.